Pengaruh penambahan bubuk temulawak (Curcuma xanthorrhiza Roxb.) dan variasi waktu pemanggangan terhadap sifat fisik, kimia dan kesukaan snack bar - Febi Prasetyo; Dwiyati Pujimulyani; Bayu Kanetro (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Indonesia is a country with rich biodiversity, including javanese turmeric (Curcuma xanthorrhiza Roxb.), which can be used as a food additive, such as in snack bars. The research aims to determine the optimal addition of javanese turmeric powder and baking duration for snack bars with the best antioxidant properties. The study employs a completely randomized design (CRD) with two factors: variations in javanese turmeric powder addition (1.5, 3, and 4.5 g) and baking duration (20, 25, and 30 minutes). The best treatment identified from the research is the addition of 3 g of javanese turmeric powder and a baking duration of 20 minutes, showing significant differences in texture, color, and overall preference. The color preference scores at 3.40, aroma at 3.20, taste at 3.16, texture at 3.48, and overall rating at 3.32. Chemical analysis of the selected snack bars resulted in a water content of 5.66%, protein content of 8.16%, and antioxidant activities measured by DPPH (1,1-Diphenyl-2-Pickrylhydrazyl) and FRAP (Ferric Reducing Antioxidant Power) at 60.92% and 10.48 mg E ferro/g, respectively. Additionally, the phenolic content was found to be 50.49 mg GAE/g. These findings indicate that snack bars with added javanese turmeric exhibit health-promoting antioxidant properties.